2020
DOI: 10.1016/j.jgo.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Treatment decision-making in chronic lymphocytic leukaemia: Key factors for healthcare professionals. PRELIC study

Abstract: To explore the preferences of Spanish healthcare professionals (haematologists and hospital pharmacists) for the treatment selection of active Chronic Lymphocytic Leukaemia (CLL) patients at first relapse, condition that mainly afflicts older adults. Methods: A discrete choice experiment (DCE) was conducted among haematologists and hospital pharmacists. A literature review and a focus group informed the DCE design. CLL treatment settings were defined by seven attributes: four patient/disease-related attributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Most studies reported coefficients (n = 72, 91%; e.g. [37,51,60,80,98]), with 17% (n = 12) of those reporting no other output measure. Behavioural outputs included marginal rates of substitution (n = 36, 46%; e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies reported coefficients (n = 72, 91%; e.g. [37,51,60,80,98]), with 17% (n = 12) of those reporting no other output measure. Behavioural outputs included marginal rates of substitution (n = 36, 46%; e.g.…”
Section: Resultsmentioning
confidence: 99%
“…[54,63,77,90,113]) or mixed or random parameter logit (n = 29, 37%; e.g. [37,47,60,76,88]), as well as latent class logit (n = 6, 8%; e.g. [40,50,53,57,100]), hierarchical bayes (n = 7, 9%; e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Also, efficacy was characterized by a very high RI, although second to cost, in a DCE experiment evaluating hematologists’ and pharmacists’ preferences for treatment selection for CLL, showing a consistent evaluation of this attribute from a clinical and service organization perspective. 10 The relative weight of the risk of serious infections was identical in the 2 groups of our DCE. Le et al 11 also found that the risk of infections was important, yet not more than that of atrial fibrillation or treatment discontinuation due to adverse events.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, the conjoint analysis may help to compare preferences of the different actors involved in CLL management, finding commonalities and inconsistencies, which may be valued in organizational perspectives. 10 , 11 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, given the high costs of these new treatments, physicians need to assess which drugs or combinations provide the best value for patients and the healthcare system and are thus worth pursuing (1). In publicly-funded National Healthcare Systems, prescribing physicians can be considered as serving a dual role, acting as patients' advocates but also as society's gatekeepers of the use of resources (58). We found that, despite cost (for the healthcare system) being the attribute with lower RI, it has an influence on oncologists' (although not for patients) preferences.…”
Section: Discussionmentioning
confidence: 84%